NIOSOMES AS AN APPROACH TO IMPROVE THE SOLUBILITY AND BIOAVAILABILITY OF BCS CLASS II DRUGS - SAWANT, GAURANG; BHAGWAT, GEETA (International Journal of Applied Pharmaceutics, 2021)
Based on their solubility and permeability, drugs are typically divided into four classes (Classes I–IV) according to the biopharmaceutics classification system (BCS). Of these classes, BCS class II drugs have high permeability and low solubility; not only do these characteristics constitute the rate-limiting step in the formulation of these drugs but the low solubility in water results in low bioavailability. Thus, methods for improving their solubility have been developed using lipid carriers such as liposomes, niosomes, and aquasomes; other approaches include self-micro-emulsifying drug delivery systems (SMEDDS) and self-nano-emulsifying drug delivery systems (SNEDDS). Currently, niosome-based drug delivery systems that utilize nonionic surfactants, drugs, and cholesterol in varying ratios are being widely used to deliver both hydrophilic and lipophilic drugs in addition to several other applications of niosomes.